Migraine and stroke. Issue 3 (29th May 2017) - Zhang, Yonghua; Parikh, Aasheeta; Qian, Shuo
Abstract : Migraines are generally considered a relatively benign neurological condition. However, research has shown an association between migraines and stroke, and especially between migraine with aura and ischaemic stroke. Patients can also suffer from migrainous infarction, a subset of ischaemic stroke that often occurs in the posterior circulation of younger women. The exact pathogenesis of migrainous infarct is not known, but it is theorised that the duration and local neuronal energy level from cortical spreading depression may be a key factor. Other factors contributing to migrainous infarct may include vascular, inflammatory, endothelial structure, patent foramen ovale, gender, oral contraceptive pill use and smoking. Vasoconstrictors such as the triptan and ergot class are commonly used to treat migraines and may also play a role. Migraine is also shown to be correlated to haemorrhagic stroke, although studies do not demonstrate causation versus association, and further studies are warranted. There are also some rare genetic diseases such as cerebral autosomal-dominant arteriopathy with subcortical infarcts and leukoencephalopathy, retinal vasculopathy with cerebral leukodystrophy and others, which can cause both migraines and infarcts. On imaging, many migraineurs are found to have white matter changes similar to those seen in patients with stroke. These may be caused in part by alterations in resting cerebral blood flow and vasoconstrictor use. In treating patients with migraines, it is important to identify and modify any vascular risk factors such as hypertension, smoking, oral contraceptive pill use and lifestyle factors. Further studies will determine if more aggressive treatment of migraines can ultimately lead to fewer strokes in this population.